Propriedades da superfície de resinas compostas com sistema de cor simplificado submetidas a desafios erosivos/abrasivos: estudo in situ - Mejía, Verónica Cecilia (2025)
Composite resins, commonly used to restore surfaces affected by dental wear, are impacted by the physical mechanisms that cause these lesions. The most recent options for these materials, featuring simplified color systems, such as monochromatic and universal, aim to provide greater clinical practicality than traditional systems of conventional color. This study evaluated in situ the physical properties of monochromatic (Palfique® Omnichroma), universal (Filtek® Universal A2), and conventional (Filtek® Z350 XT A2B) composite resins, subjected to cycles of erosion, with or without abrasion, and pigmentation in a coffee solution. With prior approval from the research ethics committee and following sample size calculations, 15 volunteers were selected based on inclusion and exclusion criteria. For 14 days, each participant used an acrylic palatal device with four composite resin discs from each group fixed on the external surface, measuring 5x2 mm (diameter and height). Daily, at scheduled times, the device was immersed extraorally in 60 mL of hydrochloric acid (three times per day: twice for 10 minutes and once for 1 hour). The first two erosive cycles of the day were followed by manual brushing of the samples fixed on the marked half of the device (twice a day for 15 seconds), and once a day, the entire device was immersed in 50 mL of coffee (for 10 minutes). The composite resin discs were evaluated for surface microhardness, roughness, wear, and color stability. Surface morphology was analyzed by scanning electron microscopy (SEM). A two-way ANOVA was used for data comparison, and Tukey's post hoc test was used when necessary, with a significance level of 5%. The results show that the level of wear (p≤0.001) and surface microhardness (p≤0.001) were statistically different among groups. There was no significant difference in roughness or color variation between types of composite resins (p>0.05). The combination of erosion and abrasion resulted in greater surface roughness (p=0.013) across all materials, with more pronounced alterations observed in SEM compared to erosive wear alone. The analysis of the results suggests that the formulations of the evaluated materials influence their properties and performance against erosion, whether associated with abrasion or not. On average, the values obtained after wear indicate a clinically acceptable resistance under these severe conditions, which should be corroborated in future clinical trials.